Expert View On Designing Creative Teaching Activities Based On Lantern Chinese Traditional Handwork For Preschoolers - Liu Zhe; Mohd Nazri Abdul Rahman (P3I UMSurabaya, 2024)
This study aimed to develop creative teaching activities for preschoolers using Lantern, a Chinese traditional handwork. Employing the Design and Development Research (DDR) method by Richey & Klein (2014), the study was conducted in three phases. The first phase involved developing instruments through a literature review and expert interviews. In the second phase, questionnaires were distributed to experts, and data were analyzed using the Fuzzy Delphi method with a five-point Likert scale to assess consensus through threshold (d) values. The final phase evaluated the activities based on expert feedback, with semi-structured interviews analyzed thematically. Results indicate that this innovative approach, integrating Lantern-making steps, effectively supports creative teaching and traditional handwork skills in preschoolers. Experts acknowledged its novelty and relevance for fostering creativity through cultural heritage activities.